Enoxaparin Continues to Show Clinical Benefit Vs Unfractionated Heparin for STEMI - Alexander, Lori (MD Conference Express, 2007)
One-year results of the ExTRACT-TIMI 25 trial continued to show significant benefits in favor of adjunctive treatment with enoxaparin vs unfractionated heparin in reducing the rate of death or nonfatal myocardial infarction in 20,479 patients with ST-elevation myocardial infarction treated with fibrinolysis.